NUSANTARA DARI SATU KAWASAN SAMPAI NAMA IBU KOTA NEGARA - Amanan Amanan (Ensiklopedia of Journal, 2022)
The Southeast Asia region we know today, in ancient times known as "Nusantara". The word "Nusantara" was first uttered by Patih Amangkubhumi or Gajah Mada. This name is used to refer to the area of islands (Gugusan Pulau-pulau) which is found in Southeast Asia today, the whole race (there is) is called the Malay race and the whole island is also called "Gugusan pulau-pulau Melayu". (Hamka, 2002: 657). According to M.Sarip, the name "Kutai Kartanegara" only existed at the end of the 13th century before it was also called Nusantara. If at the present time President Jokowidodo gives the name of the new State Capital (IKN) of the Republic of Indonesia the name Nusantara, the naming can not only revive or popularize the name but also restore the name, both as the name of an area that was popular in the past as well revive the name of an area in East Kalimantan that was popular in ancient times.Keywords: Archipelago, Region, Capital City, Country